2013
DOI: 10.1016/j.dss.2012.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Whose and what chatter matters? The effect of tweets on movie sales

Abstract: a b s t r a c tSocial broadcasting networks such as Twitter in the U.S. and "Weibo" in China are transforming the way online word of mouth (WOM) is disseminated and consumed in the digital age. In the present study, we investigated whether and how Twitter WOM affects movie sales by estimating a dynamic panel data model using publicly available data and well-known machine learning algorithms. We found that chatter on Twitter does matter; however, the magnitude and direction of the effect depend on whom the WOM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
192
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 306 publications
(207 citation statements)
references
References 17 publications
5
192
0
3
Order By: Relevance
“…Empirical research confirmed that consumers rely heavily on the advice of others in their personal network when making purchase decisions [19,36,32,20,33] and that positive WOM has a positive effect on business outcomes, i.e. sales [31,3]. Referral marketing has become an important marketing technique to stimulate WOM in a controlled way for acquiring new customers [5].…”
Section: Introductionmentioning
confidence: 93%
“…Empirical research confirmed that consumers rely heavily on the advice of others in their personal network when making purchase decisions [19,36,32,20,33] and that positive WOM has a positive effect on business outcomes, i.e. sales [31,3]. Referral marketing has become an important marketing technique to stimulate WOM in a controlled way for acquiring new customers [5].…”
Section: Introductionmentioning
confidence: 93%
“…Based on a general consensus, people's attitude toward products and purchasing them can be increased or decreased by exposure to positive and negative UGC respectively [20]. For instance, positive WOM on twitter is positively associated with movie sales and negative WOM on twitter is negatively associated with movie sales [26]. Accordingly, we propose following hypotheses:…”
Section: Theoretical Foundation and Hypothesesmentioning
confidence: 99%
“…They showed that NN achieves better performance than SVM on balanced datasets. Rui and Liu [20] investigated pre-consumer (prior to purchase) and post-consumer (after purchase) opinion differences using NB and SVM classifiers on twitter data from both classes of users. Li and Li [21] addressed subjectivity and expresser credibility in opinion studies using SVM as the classifier.…”
Section: A Sentiment Analysis In Genaralmentioning
confidence: 99%
“…As we can see from the above [24], [29], [70] 2 SVM + NB [7], [9], [10], [11], [27], [39], [41], [42], [48] Also we can see that the Saudi dialect was not given attention by the researchers. [2], [3], [4], [5], [6], [9], [13], [19], [20], [22], [23], [24], [33], [39], [41], [42], [46], [48], [49], [65], [70] 2 MSA (Egyptian) [7], [10], [11], [21], [27], [28], [51], [70] 3 MSA (Levantine) [7] 4 MSA (Khaliji) [7], [11], [65] 5 MSA (Arabizi) [7] 6 MSA (Mesopotamian) [11] 7…”
Section: B Arabic Sentiment Analysismentioning
confidence: 99%
See 1 more Smart Citation